(3cJGH GdeSJZjKjf HGddg JYGdi YfO GdegeGJ hGdMGLGJs - (3GHf HTchGd , Nda Hf YHO Gdedc Hf eSYhO Hf HTchGd GdNRQLj GdCfUGQj, CHhGdbGSe,J (B578 (3g` s
(3ChdgG (B:s
(3Gddge ELYdfG eef GSJZGK Hc aCZKfg hOYGc aCLHJg bGd deG cGf jhe HOQ fXQ QShd Gddg Udi Gddg Ydjg hSde GdeTQcjf hge Cda s
(3BNQgG (B:s
(3hbGd SajGf Yf GdCYeTi Yf GdMce , cGf Gdfed ai ReGf SdjeGf Ydjg GdSdGe CeKGd GdPHGH GdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(242 / 4 (3b(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs